2020
DOI: 10.1029/2019wr025910
|View full text |Cite
|
Sign up to set email alerts
|

A Network Approach for Delineating Homogeneous Regions in Regional Flood Frequency Analysis

Abstract: Regional flood frequency analysis forms the basis for ascertaining design thresholds for extreme flow events for the purpose of resource management and design of hydraulic structures, especially at ungauged or partially gauged basins. A crucial step in this analysis is transferring available information from gauged sites to ungauged sites, which is achieved through delineation of homogeneous regions encompassing multiple catchment locations, followed by the formulation of a flood estimation model. While this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Haddad et al (2012) showed that the ROI approach leads to more efficient and accurate flood quantile estimates compared to the fixes regions approach. Another such technique, Canonical Correlation Analysis (CCA), has been used for delineating homogenous regions in a number of studies ( See for instance Ouarda et al, 2000;Han et al, 2020). In the present study, CCA is used to delineate homogenous regions as Ouarda et al (2008) indicated that it leads to superior performances.…”
Section: Introductionmentioning
confidence: 79%
“…Haddad et al (2012) showed that the ROI approach leads to more efficient and accurate flood quantile estimates compared to the fixes regions approach. Another such technique, Canonical Correlation Analysis (CCA), has been used for delineating homogenous regions in a number of studies ( See for instance Ouarda et al, 2000;Han et al, 2020). In the present study, CCA is used to delineate homogenous regions as Ouarda et al (2008) indicated that it leads to superior performances.…”
Section: Introductionmentioning
confidence: 79%
“…Furthermore, each of the regionalization approaches (ROI, CCA, CA) considered in this study has several variants. One could attempt preparing ensembles corresponding to different variants of ROI (e.g., Cunderlik & Burn, 2006; Durocher et al., 2018; Formetta et al., 2018; Mostofi & Burn, 2019; Zrinji & Burn, 1996), CCA (e.g., Han et al., 2020; Ouali et al., 2016; Ouarda et al., 2000; Ribeiro‐Corréa et al., 1995; Shu & Ouarda, 2007), and CA (e.g., Basu & Srinivas, 2014, 2016; Cassalho et al., 2019; Farsadnia et al., 2014; Rao & Srinivas, 2006a; Wazneh et al., 2015) for investigating improvement in regions derived by application of FEC to those individual ensembles and their possible combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Some methods include kernel‐based fuzzy c‐means cluster (FCM) and entropy‐based clustering (Basu & Srinivas, 2014, 2015). Han et al (2020) used a network approach for delineation on 202 catchments in Australia, while Jothiprakash et al (2021) applied FCM‐based regional flood frequency analysis to 43 watersheds of west‐flowing rivers in Kerala, India. Zalnezhad et al (2022) used adaptive neuro‐fuzzy inference system (ANFIS) using data from 181 gauged catchments in south‐eastern Australia for non‐linear regional flood frequency analysis.…”
Section: Methodsmentioning
confidence: 99%